Physical and mechanical properties of fiberboard made from corn cob and coconut fiber with natural adhesives - Hasanah, Moraida; Marlina, Hilda Ayu; Zahar, Intan; Kadir, Abdul Azis (Jurnal Polimesin, 2024)
Developing fiberboard from agro-industrial and natural waste has a significant impact on environmental practices. Fiberboards made from corncobs and coconut fiber have become a desirable by-product that can serve as a wood substitute. This research aims to analyze the physical and mechanical properties of fiberboard composites created from coconut husks and corn cobs, using natural adhesives like tapioca glue and citric acid. Corn cob particles and coconut fruit fibers were weighed in a 1:1 ratio. Tapioca glue or citric acid was then added in varying percentages: 10%, 14%, 18%, 22%, and 26% of the total mixture. This blend was poured into molds, spread evenly with a spatula, and pressed under 30 kg/cm² (426.7 psi). Subsequently, the samples were carefully removed for physical and mechanical testing. The findings of the study indicated that the different mass variations of corncobs and coconut fibers mixed with natural adhesives successfully produced fiber composites that met the Japanese Industrial Standards (JIS) A 5095:2003 for the "hardboard" classification. The most effective composition was found in sample A5, which contained 26% tapioca glue. Tapioca glue proved to be the superior natural adhesive, surpassing citric acid. Tests conducted on fiberboard A5 revealed the highest density at 0.90 gr/cm³, the lowest porosity at 7.35%, optimal impact strength at 119.99 J/m², tensile strength of 730.50 MPa, and flexural strength of 109.34 MPa. Therefore, this fiberboard demonstrated favorable physical and mechanical properties.